Efficacy of medical dissolution for suspected struvite cystoliths in dogs. (1st September 2021) - Wingert, Allie M.; Murray, Olivia A.; Lulich, Jody P.; Hoelmer, Alexis M.; Merkel, Lindsay K.; Furrow, Eva
Abstract: Background: Medical dissolution of struvite uroliths in dogs is commonly recommended, but data on success rates and complications are limited. Objectives: To evaluate the efficacy of medical dissolution for suspected struvite cystoliths in dogs. Animals: Fifty client‐owned dogs fed a therapeutic dissolution diet, with or without administration of antimicrobials, for treatment of suspected struvite cystoliths. Methods: Single institution, retrospective case series. Medical records were reviewed for dogs with at least 1 follow‐up visit. Dissolution success, complications, and possible predictors of success were evaluated. Results: Full dissolution of cystoliths was achieved in 58% (29/50) of dogs within a median of 35 days (range, 13‐167). Of 21 dogs without success, 7 each had partial dissolution, no dissolution, or undetermined outcome. Uroliths containing >10% nonstruvite mineral were common in the nonsuccess group (11/16 analyzed). Maximum urolith diameter, number of uroliths, and baseline urine pH did not differ significantly between dogs with and without success. Dissolution was more likely in dogs receiving antimicrobial therapy (OR = 16.3, 95% confidence interval 1.9‐787.4, P  = .002). Adverse events occurred in 9 dogs (18%); urethral obstructions were the most common, but 3 of 4 dogs with this complication were obstructed on presentation, before trial initiation. Conclusions and Clinical Importance: Results support a medical dissolution trial for dogs with suspected struvite cystoliths. If no reduction in urolith size or number occurs by 1 month, a nonstruvite composition is likely, and alternative interventions should be considered. Dogs presenting with urethral obstructions should not be considered candidates for medical dissolution.